Improving nurses' knowledge, practice, and self-efficacy regarding caring patients with tuberculosis: A quasi-experimental design - Samia Eaid Elgazzar; Mirfat Mohamed Labib Elkashif; Mohamed Goda Elbqry; Fatma Mohamed Elmansy (Wolters Kluwer Medknow Publications, 2023)
Background: Tuberculosis (TB) control depends on healthcare professionals 'knowledge, practice, and self-efficacy when managing high-risk groups. So the study aimed to evaluate the effectiveness of a structured educational program in improving nurses' knowledge, practice, and self-efficacy in caring for patients with TB. Material and Methods: A pre-test post-test quasi-experimental design was conducted on 36 nurses at Chest hospital Al Masah al Bahri in port said city and the Chest Hospital in Damietta City, Egypt. Data were collected using three self-administered questionnaires to assess knowledge, practice, and self-efficacy by using convenience sampling from March to August 2019. Data analyses were done by using a paired t-test, a Student t-test, and an F-test analysis of variance. Results: Based on data related to the two groups before and after the study in knowledge, practice (t = 8.27, p < 0.001), and self-efficacy (t = 28.91, p < 0.001), there was a significant difference between knowledge and overall knowledge scores (t=14, p < 0.001). Mean scores were significantly increased for practice items about the nursing role in medication, directed observed therapy, and the overall practice score; and for self-efficacy, which increased from 27.58 to 37.86 (p = <0.001). The results indicate that nurses' knowledge, practice, and self-efficacy were enhanced by the implementation of the educational program. Conclusions: There is scope for development in knowledge, practice, and self-efficacy using the educational program among nurses. Training programs must be implemented in quality control to aid nurses in realizing the significance of information in reducing disease and death and enhancing the quality of care.